The Path to Sensory Readiness: How Age and Gender Influence Sensory Development in Early Childhood - E, Akshaya; Vikraman, Nisha (THE PRIMARY TEACHER, 2025)
This study examines the sensory readiness in Anganwadi children aged 4–6 years in Kannur district, Kerala. It focuses on the impact of age and gender on sensory readiness, which is crucial for success in a learning environment. The research uses a cross-sectional design with 189 Anganwadi children. A self-designed observational scale was used for collecting the data. Results show high sensory development readiness, with an average score of 84.20 per cent. Gender examination indicates that there is no notable variation in sensory readiness between boys and girls. Age-based evaluation categorises children into four groups—4–4.5, 4.5–5, 5–5.5 and 5.5–6 years. The study found that there were no significant variations in sensory development readiness among these age ranges.